Antibacterial and antitumor activities of chitosan/polyvinyl alcohol films containing microemulsion of papaya seed essential oil. (June 2022) - Yi, Guohui; Yin, Chunxiao; Lao, Yuli; Shi, Zaifeng; He, Xiaowen; Wu, Jinyan; Jiang, Yueming; Gong, Liang
Abstract: Biodegradable functional films using chitosan (CS) and polyvinyl alcohol (PVA) containing 0.125–1% w/w Carica papaya seed essential oil (CPEO) were prepared by casting and solvent evaporation, and their mechanical and optical properties were investigated. The results showed that CPEO decreased the mechanical properties of the composite film but without significant effects at concentrations of 0.125% and 0.25%. The incorporation of CPEO into the CS/PVA film provoked an effective shield against UV light, suggesting excellent properties for preventing lipid food oxidation. Furthermore, CPEO, composed mainly of benzyl isothiocyanate (BITC) was confirmed by gas chromatography/mass spectrometry, and some insights into chemical bond interactions among the ternary blends were revealed using Fourier transform infrared (FTIR) spectroscopy and X-ray diffraction (XRD) analyses. In addition, the CS/PVA/CPEO films showed strong inhibitory activity against Salmonella aureus and Escherichia coli, which was greater than the inhibitory activity of the commercialized antibiotic carbenicillin disodium. The testing also demonstrated that the composite film possesses promising cytocompatibility with two human normal cells but high cytotoxicity against four human tumour cells. These results suggest that CS-based PVA films incorporated with CPEO have potential applications in the biomedical field. Graphical Abstract: ga1 Highlights: CS/PVA films containing CPEO were prepared by casting and solvent evaporation. The physico-chemical properties were demonstrated by FTIR, XRD and SEM. The composite film provoked an effective shield against UV light. Antibacterial activity of the composite film was stronger than carbenicillin disodium. The cytotoxicity of CS/PVA/CPEO films was tested against human normal and tumour cells.